Distinct muscle growth and strength adaptations after preacher and incline biceps curls - Kassiano, Witalo; Costa, Bruna; Kunevaliki, Gabriel; Lisboa, Felipe; Stavinski, Natã; Prado, Aline; Tricoli, Ian; Francsuel, Jarlisson; Lima, Luis; Nunes, JoãoPedro; Ribeiro, Alex Silva; Cyrino, Edilson S. (International Journal of Sports Medicine, 2025)
We compared performing preacher and incline biceps curls on changes in elbow flexor muscle size and strength. This was a between-group repeated measure randomized trial. Sixty-three young women performed the preacher biceps curl (n=30) or the incline biceps curl (n=33) for 8 weeks, twice a week. We measured the muscle thickness of elbow flexors at the proximal, middle, and distal sites. We assessed the muscle strength using three repetition maximum tests in the preacher curl and the incline curl. We observed a greater increase in the proximal elbow flexor thickness in the incline biceps curl compared to the preacher biceps curl (mean difference=0.08 cm [95% confidence interval: 0.02, 0.13 cm]). We observed a greater increase in the distal elbow flexor thickness in the preacher biceps curl compared to the incline biceps curl (mean difference=0.10 cm [95%CI: 0.04, 0.15 cm]). The preacher biceps curl showed a greater increase in three repetition maximum tests in the preacher curl (mean difference=1.88 kg [95%CI: 1.14, 2.62 kg]). The incline biceps curl showed a greater increase in three repetition maximum tests in the incline biceps curl (mean difference=0.86 kg [95%CI: 0.10, 1.62 kg]). Our findings suggest regional differences in muscle growth induced by the preacher and incline biceps curls. Strength gains appear to follow the principle of specificity.
Keywords: exercise selection; muscle growth; resistance training; biceps brachii